Association of mitochondrial DNA polymerase γ gene POLG1 polymorphisms with parkinsonism in Chinese populations. - Ya-xing Gui (Public Library of Science (PLoS), 2012)
Background Mitochondrial DNA polymerase gamma (POLG1) mutations were associated with levodopa-responsive Parkinsonism. POLG1 gene contains a number of common nonsynonymous SNPs and intronic regulatory SNPs which may have functional consequences. It is of great interest to discover polymorphisms variants associated with Parkinson's disease (PD), both in isolation and in combination with specific SNPs. Materials and methods We conducted a case-control study and genotyped twenty SNPs and poly-Q polymorphisms of POLG1 gene including in 344 Chinese sporadic PD patients and 154 healthy controls. All the polymorphisms of POLG1 we found in this study were sequenced by PCR products with dye terminator methods using an ABI-3100 sequencer. Hardy-Weinberg equilibrium and linkage disequilibrium (LD) for association between twenty POLG1 SNPs and PD were calculated using the program Haploview. Principal results We provided evidence for strong association of four intronic SNPs of the POLG1 gene (new report: c.2070-12T>A and rs2307439: c.2070-64G>A in intron 11, P = 0.00011, OR = 1.727; rs2302084: c.3105-11T>C and rs2246900: c.3105-36A>G in intron 19, P = 0.00031, OR = 1.648) with PD. However, we did not identify any significant association between ten exonic SNPs of POLG1 and PD. Linkage disequilibrium analysis indicated that c.2070-12T>A and c.2070-64G>A could be parsed into one block as Haplotype 1 as well as c.3105-11T>C and c.3105-36A>G in Haplotype 2. In addition, case and control study on association of POLG1 CAG repeat (poly-Q) alleles with PD showed a significant association (P = 0.03, OR = 2.16) of the non-10/11Q variants with PD. Although intronic SNPs associated with PD didn't influence POLG1 mRNA alternative splicing, there was a strong association of c.2070-12T>A and c.2070-64G>A with decreased POLG1 mRNA level and protein levels. Conclusions Our findings indicate that POLG1 may play a role in the pathogenesis of PD in Chinese populations.